Penataan Masterplan Bukit Doa Maria Watu Blencong Sebagai Upaya Pengembangan Wisata Religi Inklusif dan Berkelanjutan - Yustina Banon Wismarani; Mutiara Cininta; Sebastianus Adjie Sindhunata; Michael Grace Susanto (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2025)
This community service activity aims to design a master plan for the Watu Blencong Maria Prayer Hill area in Kalibawang, Kulon Progo, as an inclusive, safe, and spiritually meaningful Catholic pilgrimage site. This area has strong natural potential in the form of hilly contours, sacred natural stones called Watu Blencong, and unique light orientation, but has not been arranged functionally and symbolically. The design approach was carried out through a participatory method involving parish administrators, congregations, and the local community in three stages of discussion forums (initial, interim, and final reports). The main concept developed was